Gambaran Tingkat Kebersihan Gigi Mulut Menurut Kebiasaan Menyikat Gigi Pada Siswa Kelas Iv Di Sdn Panyileukan 268 - Billa, Anisa Salsa; Nurjanah, Neneng; Laut, Deru Marah; Hendriani Praptiwi, Yenni; Ningrum, Nining (Jurnal Terapi Gigi dan Mulut, 2023)
The low level of dental hygiene has the potential to bring about various dental and oral problems in children. One of the simplest ways to maintain good dental hygiene is to perpetuate a good brushing habit. Indicators of brushing habits include frequency, time, and how to brush your teeth. This study aims to describe the level of dental and oral hygiene of fourth grade students at Panyileukan 268 Elementary School according to their brushing habits. This study included checking the level of dental hygiene using the Hygiene Index Plaque Control Score method and distributing questionnaires to determine the brushing habits of fourth grade students at Panyileukan 268 Elementary School. This type of research was an observational study with a descriptive approach. The population of this study were fourth grade students at SDN Panyileukan 268. The research sample was taken randomly using simple random sampling technique. After being analyzed by the cross tabulation method, the results of this study showed that most of the respondents who had a poor habit of brushing on each indicator, also had poor dental hygiene levels. In the frequency indicator, most of the respondents who brush their teeth only once a day (bad criteria) have poor dental hygiene levels. In the time indicator, most of the respondents who brush their teeth only after breakfast or before going to bed (bad criteria) have poor dental hygiene levels. And on the indicator of how to brush their teeth, most of the respondents who brush their teeth without a combination movement (bad criteria) have a poor level of dental hygiene.